(untitled) (Journal of Hama University, 2020)
This study was conducted on (80) hamsters, and aimed to determine the effect of different concentrations of aqueous and alcoholic extract of nettle plant (urtica dioica) on the level of sugar in hamsters with diabetes experimentally by alloxan, used (8) groups, where each group included (10) animals, left The first group as a natural control, while the other groups were injected with alloxan to induce experimental diabetes, the first group (G1) was given only water and food (control), while the aqueous extract was administered at a dose of (250) mg / kg for the second group (G2), and in a dose (250) mg / kg of alcoholic extract of the third group (G3), at a dose of (500) mg / kg ,the aqueous extract of the fourth group (G4), with a dose (500) mg / kg of the alcohol extract of the fifth group (G5), and a dose (750) mg / kg of the aqueous extract for the sixth group (G6), and at a dose (750) mg / kg of the extract Alcohol for G7, while G8 was not treated with any type of extract (negative control). The results showed that treatment with aqueous and alcoholic extract of nettle plant caused in a significant decrease (P 0.05) in the level of sugar in groups with diabetes compared with the negative control group (G8). There were no significant differences when comparing the dosage concentrations of the aqueous and alcoholic extracts.